2013
DOI: 10.1007/s10863-013-9526-8
|View full text |Cite
|
Sign up to set email alerts
|

Tl+ induces both cationic and transition pore permeability in the inner membrane of rat heart mitochondria

Abstract: Effects of Tl(+) were studied in experiments with isolated rat heart mitochondria (RHM) injected into 400 mOsm medium containing TlNO3 and a nitrate salt (KNO3 or NH4NO3) or TlNO3 and sucrose. Tl(+) increased permeability of the inner membrane of the RHM to K(+) and H(+). This manifested as an increase of the non-energized RHM swelling, in the order of sucrose < K(+) < NH4 (+), respectively. After succinate administration, the swollen RHM contracted. The Tl(+)-induced opening of the mitochondrial permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…However, these organelles are extremely susceptible to oxidative stress, which triggers mutations in the mtDNA and regulates the membrane permeability [34]. Furthermore, past studies have also supported the involvement of mitochondrial dysfunction in AS development [35-37].…”
Section: Discussionmentioning
confidence: 99%
“…However, these organelles are extremely susceptible to oxidative stress, which triggers mutations in the mtDNA and regulates the membrane permeability [34]. Furthermore, past studies have also supported the involvement of mitochondrial dysfunction in AS development [35-37].…”
Section: Discussionmentioning
confidence: 99%
“…The heart apex of rats in the AT1R-shRNA group was injected with 0.1 mL of Ad5-AT1R-shRNA and the NC group with 0.1 mL of Ad5-EGFP, whereas the sham group and the model group with 0.1 mL of diluted phosphate-buffered saline (PBS) containing recombinant virus. 23 During 10-s blocking circulation, the mice presented with gradually decreasing heart rate and decreased ventricular wall motion without ventricular fibrillation.…”
Section: Transfection Of Adenovirus Expression Vectormentioning
confidence: 99%
“…Finally, the cells were stained with 4′,6-diamidino-2-phenylindole, incubated at room temperature for 15 minutes and observed under a fluorescence microscope. 23 2.10 | Extraction of myocardial mitochondria and analysis of swelling and membrane potential in rats After the rats were killed, about 100-mg myocardial tissue blocks were placed on ice, sliced into pieces, and added with a precooled homogenate medium A solution (including 250 mmol/L of sucrose, 0.1 mmol/L of ethylene glycol tetraacetic acid (EGTA), 2 mmol/L of 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), and 5 mg/L of calf serum protein, pH 7.2) to make 10% tissue homogenate on ice using a homogenizer using a 1:9 ratio. Next, the homogenate was centrifuged at 1500 rpm for 10 minutes at 4°C, and the precipitate was discarded.…”
Section: Detection Of Antioxidant Capacity Of Myocardial Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al showed that the potential of the mitochondrial membrane is higher than normal levels, and the mitochondrial ROS level is abruptly reduced during ischemia-reperfusion injuries [7]. Under the influence of oxidative stress, mtDNA mutations easily occur in the mitochondria, thus altering the permeability of the cell membrane [11]. Experimental studies conducted by Zhang et al have shown that the activation of Nrf2 can reduce the degree of oxidative stress in the mitochondria and can reduce the oxidative stress and inflammatory response of vascular endothelial cells [12].…”
Section: Nrf2/ho-1 Signaling Axis In Mitochondrial Oxidativementioning
confidence: 99%